ANALISIS KEUNTUNGAN USAHA “BAGEA SAGU” KHAS KOTA TERNATE (STUDI KASUS TOKO PUSPA KENCANA KELURAHAN FALAJAWA 1 KECAMATAN TERNATE TENGAH KOTA TERNATE (Business Profit Analysis of "Bagea Sagu" Typical of Ternate City) (Case Study of Puspa Kencana Shop) - Iis Marsindi Ruslan; Noortje M. Benu; Ribka M. Kumaat (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2023)
The purpose of this research is to analyze the profit of the "Bagea Sagu" business. The research method used is a case study in the UMKM business "Bagea Sagu". The data used are primary and secondary data. collecting data in this study using interviews and documentation techniques. The interview was conducted by directly interviewing the business owner of "Bagea Sagu" Typical of Ternate City as a respondent using a list of question that had been prepared previously (questionnaire). Documentation is done by collecting data related to research both from relevant agencies and the internet. The results of the study showed that the "Bagea Sago" business typical of Ternate City incurred a total production cost of Rp. 4,652,187 with the level of profit obtained by the "Bagea Sago" business typical of Ternate City from processing raw materials into finished products that have been packaged until product marketing of Rp 3,447,813 and if you use the R/C ratio, the value of 1,74 which means that this business is profitable.